Clinical, Microbiological Profile and Antibiotics Use in Admitted Patients of Urinary Tract Infection - Singh, Harpreet; Suri, Vikas; Mohan, Balvinder; Mohindra, Ritin; Taneja, Neelam; Bhalla, Ashish (Bangladesh Medical Journal, 2024)
Urinary tract infections (UTI) can vary from simple cystitis to pyelonephritis with severe sepsis. The objective of this study is to provide information about the clinical and microbiological profile of admitted patients of urinary tract infection, patterns of organisms isolated, antibiotic sensitivity pattern and antibiotics use. It was a prospective observational study conducted on 40 patients age >14 years admitted with diagnosis of UTI based on clinical and microbiological criteria over 8 months at a tertiary care hospital in North India. Data was collected for the clinical, microbiological profile, empirical and definite antibiotics use with duration of stay and outcome of patients. Among 40 cases of UTI; male to female ratio was 1:1 with mean age of 51.3± 16.32 years. Fever was present in almost all (97.5%) of the patients and three-fourth (75%) of them had dysuria. Type-2 Diabetes Mellitus was most common (55%) underlying condition and mean HbA1c was 9.37±2.27 followed by obstructive uropathy (17.50%). Most of cases (82.5%) were of complicated UTI; where Pyelonephritis was 42%, Emphysematous Pyelonephritis 12.5% and Renal Abscess 7.5%. Most common (37.5%) organism isolated from urine/ pus culture was Escherichia coli. More than half of the patients (55%) were given empirical antibiotics injection piperacillin tazobactam and carbapenems was used in more than one third (35%) of patients. The mean duration of antibiotics use was 14.55±4.94 days. Two (5.0%) patients expired out during the study period. Uncontrolled Diabetes Mellitus remains the major underlying condition in cases of complicated UTI. E coli is the most common organism isolated from urine/ pus culture. Most of the patients had favourable outcome with guided antibiotics and interventions. Bangladesh Med J. 2023 May; 52(2): 15-19